(untitled) (Ameghiniana, 2014)
The palaeoenvironmental evolution of the Loma Negra section (Bardenas Reales de Navarra, Ebro Basin) during the lower–middle Miocene, is studied for the first time. The paleoenvironmental interpretation is based on the recovered ostracod assemblages and the sedimentology. The lower part of this section is composed by red, yellow and grey mudstones, and with Paralimnocythere sp. as the most abundant ostracod taxon. The lithological features and the faunistic assemblage allows the interpretation of a paleoenvironment with the development of shallow water bodies with stagnant, warm and fresh to oligohaline waters in distal alluvial flood plains for this section. The presence of some sandstone levels where the most abundant ostracod species is Cyclocypris laevis (Müller) marks punctual higher energy events inside this alluvial system and the presence of more saline waters. The upper part of the section is formed by grey limestones with interbedded fine grey mudstones. In this interval, Pseudocandona parallela Müller is the most abundant ostracod species, indicating the development of a stable lacustrine system with water currents, and temperate to cold and oligohaline to mesohaline waters. The transition between the alluvial and the lacustrine systems shows a gradual evolution.